2019
DOI: 10.4314/ovj.v9i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Supposed endogenous endophthalmitis caused by <i>Serratia marcescens</i> in a cat

Abstract: An 8-year-old male neutered domestic shorthair cat was presented for evaluation of acute respiratory distress. Respiratory auscultation revealed a diffuse and symmetric increase in bronchovesicular sounds. Thoracic radiographs showed a diffuse unstructured interstitial pulmonary pattern with multifocal alveolar foci. Despite an aggressive treatment with supportive care, including oxygenotherapy and systemic antibiotics, progressive respiratory distress increased. Three days after the presentation, acute anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(31 reference statements)
2
1
1
Order By: Relevance
“…All S. marcescens isolates were resistant to cefazolin, cephalexin, cefuroxime, amoxcillin, amoxicillin/clavulanic acid, chloramphenicol, and enrofloxacin. A previous case report of S. marcescens endogenous endophthalmitis in a cat found no resistance to fluoroquinolones differing from our study 15 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…All S. marcescens isolates were resistant to cefazolin, cephalexin, cefuroxime, amoxcillin, amoxicillin/clavulanic acid, chloramphenicol, and enrofloxacin. A previous case report of S. marcescens endogenous endophthalmitis in a cat found no resistance to fluoroquinolones differing from our study 15 …”
Section: Discussioncontrasting
confidence: 99%
“…A second aim was to determine if an IV antibiotic at the time of induction was associated with a lower prevalence of a positive culture result in comparison with an aseptic preparation alone. We found that administration of IV cefazolin was not significantly associated with a positive culture result; neither were 15 Serratia marcescens is a gram-negative bacillus ubiquitous in the environment and considered a hospital acquired pathogen sporadically identified in human neonatal intensive care units, 16,17 urinary tract infections, 18 and endocarditis. 19,20 It has intrinsic resistance to antimicrobials and disinfectants, including narrow spectrum penicillins and cephalosporins.…”
Section: Discussionmentioning
confidence: 75%
“…As for the cases of the genus Serratia as a cause of endophthalmitis in animals, there is still not much information beyond the report of a cat presenting ophthalmological examination with panuveitis, increased IOP and unsatisfactory treatment (GUYONNET et al, 2019), similar to what happened in this study.…”
Section: Discussionsupporting
confidence: 61%
“…As for cases of the genus Serratia as a cause of endophthalmitis in animals, there is still not much information other than the report of a cat presenting with panuveitis, increased IOP and unsatisfactory treatment (GUYONNET et al, 2019), similar to what happened in this study.…”
Section: Discussionsupporting
confidence: 59%